THE THOUGHTS OF RABINDRANATH TAGORE AND THE UPANISHADS ON BRAHMANISM: A COMPARATIVE ANALYSIS/ ব্রহ্মবাদ প্রসঙ্গে উপনিষদ ও রবীন্দ্রনাথের ধারণা : একটি তুলনামূলক পর্যালোচনা (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Rabindranath Tagore was familiar with the Upanishads from his childhood. The main theme of the Upanishads is Brahman. We find the concept of Brahmanism (Brahmabāda) in Rabindranath's thought which was influenced by the Upanishads. Sometimes Rabindranath explained Brahman as in the Upanishads and sometimes he also presented the concept of Brahman in a new way with his own thoughts. Like the Upanishads, Rabindranath searched for a hidden entity in Nature. Through a deep love relationship he found that the entity in his ownself is called ‘Jivan Devata’. According to Tagore, the universal entity can be manifested in two stages: firsty the entity is the all-pervasive hidden governing power, the manifestation of the actions of it. Secondly, it is revealed through the love relationship with the individual, like the Jivan Devata of the souls. The Manifestation of the work of universal entity means to act for others by being humane towards the universe. From these Rabindranath developed the theory of Humanism. There is a difference between the thoughts of Rabindranath and the Upanishads on the Jivan Devata. We find the concept of Jivan devata in the thoughts of Rabindranath, where we cannot find that in the Upanishads. Rabindranath pays more importance to the path of devotion (bhakti Marg), where the Upanishads pays the path of knowledge (gyan Marg). We will also find more importance of dualism than monism in Rabindra Darshan. In this context Dualism he gave much importance to the mind in composing the external world. Like the Upanishads, Rabindranath believed that Nirguna Brahma created the world in order to get pleasure. In this way, we will try to present that Rabindranath's Brahmanism is not completely like that of the Upanishads and also not like the theories of Vedantic philosophers. In short, in our opinion we can assume Rabindranath's concept of Brahman as a distinct Brahmanism.
Keywords: Rabindranath; Brahmanism; Upanishad; Jivan Devata; Monism; Dualism; Reality; Brahman; Vedas